Cartoons As Educational Tools And The Presentation Of Cultural Differences Via Cartoons - Ozer, Deniz; Avci, Ikbal Bozkurt (Elsevier Science Bv, 2015)
The childhood of a person is shaped as per the conditions of his/her community. However, the childhood in our technology-based era is highly overwhelmed by the ubiquitous communication devices. As a pioneering type, television achieves in grabbing children's attention by using its multi-coloured and animated world. What is more, cartoons provide the children a great load of new ideas, allowing them to enrich their dream world as well as to improve their vocabulary and learn new games. These developments are then turned to permanent behaviours. This being the case, it becomes inevitable that these habits reflect the cultural and moral values of the countries depicted in cartoons. This, in turn, makes the children absorb the linguistic and behavioural traditions of those cultures. The present study delves into two well-known cartoons, one being Turkish, called Pepee and the other Canadian, called Caillou, with a view to investigating the ways they present their cultural values. The ways of presentation were assessed using content analysis, and also the differentiating cultural elements were identified. (C) 2015 The Authors. Published by Elsevier Ltd.
Proceedings of 6th World Conference on Educational Sciences -- FEB 06-09, 2014 -- Grand Hotel Excelsior Convention Center, Valletta, MALTA
Keywords: Cartoons; education; culture; cultural differences; Pepee ve Caillou